2006
DOI: 10.1037/0022-0663.98.3.489
|View full text |Cite
|
Sign up to set email alerts
|

Reading achievement gaps, correlates, and moderators of early reading achievement: Evidence from the Early Childhood Longitudinal Study (ECLS) kindergarten to first grade sample.

Abstract: This study estimated reading achievement gaps in different ethnic, gender, and socioeconomic groups of 1st graders in the U.S. compared with specific reference groups and identified statistically significant correlates and moderators of early reading achievement. A subset of 2,296 students nested in 184 schools from the Early Childhood Longitudinal Study (ECLS) kindergarten to 1st-grade cohort were analyzed with hierarchical linear models. With child-level background differences controlled, significant 1st-gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
171
5
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 276 publications
(195 citation statements)
references
References 33 publications
12
171
5
7
Order By: Relevance
“…Entwisle et al (2007) find that the gender gap emerges relatively late in the elementary school experience. Other research, however, shows that girls have better reading skills than boys in kindergarten (Chatterji, 2006;Tach and Farkas, 2006;West, Denton, and Reaney, 2000), and that this advantage persists throughout elementary school (Trzesniewski et al, 2006;U.S. Department of Education, 2006).…”
Section: Social/behavioral Skills Academic Achievement and Gendermentioning
confidence: 99%
“…Entwisle et al (2007) find that the gender gap emerges relatively late in the elementary school experience. Other research, however, shows that girls have better reading skills than boys in kindergarten (Chatterji, 2006;Tach and Farkas, 2006;West, Denton, and Reaney, 2000), and that this advantage persists throughout elementary school (Trzesniewski et al, 2006;U.S. Department of Education, 2006).…”
Section: Social/behavioral Skills Academic Achievement and Gendermentioning
confidence: 99%
“…For instance, Meyer and colleagues (1994) revealed a negative relationship between the amounts of time kindergarten teachers spent reading and their students' reading achievement, which corroborates many previous studies reporting lowto-moderate negative correlations between teachers' reading to children and children's reading achievement. Chatterji (2006) also reported that more at-home reading time was associated with greater reading achievement among African American students. Clearly, merely reading aloud to a child is not enough, and children in kindergarten need to actively participate in reading texts themselves.…”
Section: Discussionmentioning
confidence: 97%
“…library visits) compared to boys, who tend to read less often, and think less positively about reading. Research conducted by Chatterji (2006) also shows that boys have consistently lagged behind girls in reading; from when they were enrolled in kindergarten until the end of first grade where the gap is the widest. In a broad cross-sectional study of 14,315 students, McQuillan (2013) found that the girls had more positive attitudes toward reading than the boys.…”
Section: Reading Attitudes and Gendermentioning
confidence: 99%